Endangered ethnobotanical information and germplasm from the Talamanca Mountain in Panama and Costa Rica: final report - Hazlett, D.L. (CATIE, Turrialba (Costa Rica) IBPGR Project, Turrialba (Costa Rica), 2014)
43 pág, ilus, tab, 8 ref.